Augmented Reality Application for Surgery Simulation: Circumcision Augmented Reality Simulation (CARS) - Maulana, Muhammad Sobri; Winarto, Hariyono; Amalia, Gassani (Medika Teknika : Jurnal Teknik Elektromedik Indonesia, 2020)
As one of the most common minor surgical procedure performed globally, male circumcision has some complications when performed by medically trained providers and non-medically trained providers. Presently, there is no standardized circumcision training approach, and there have been variable resources and materials used. We constructed a low-cost, and mobile circumcision training application augmented reality called Circumcision Augmented Reality Simulation (CARS). CARS is built in a computer with minimum processor 4Ghz (RAM 4GB, VGA 2GB) and smartphone with Blender, Inkscape, Audacity and Unity3D software. Features that are provided in CARS are including 3D models, animation and sound of circumcision procedure. CARS was tested through several steps including black box technique, response time loading and layer resolution examination. The trial is also done with various smartphones. The angles detected ranging from 20o-90o, with a maximum distance of 4 m using markers measuring 20x22 cm. Based on the percentage of the enclosed barrier, the marker can be detected between 0-90 percent. CARS as an example of augmented reality application for surgery simulation has been successfully built with features performing circumcision simulation and suitable for potential users (medical students and doctors). Implications for future research include assessing reliability and validity by growing its use to a broader population, creating another surgery procedure simulation with augmented reality technology using smartphone.